Acute effect of active isolated stretching technique on range of motion and peak isometric force - Vernetta Santana, M.; Ariza-Vargas, L.; Robles-Fuentes, A.; López-Bedoya, J. (The Journal of Sports Medicine and Physical Fitness, 2016)
AIM: The aim of the study was to ascertain the acute effect of stretching technique Active Isolated Stretching (AIS) over the range of active and passive movement of the hip in flexion and peak isometric force (PIF) knee flexion.